RECONSTRUCTION OF BPHTB PAYMENT ARRANGEMENTS IN THE PROCESS OF BUYING AND BUYING RIGHTS TO LAND AND/OR BUILDINGS LINKED TO THE AUTHENTICITY OF PPAT DEEDS - R.A. Nanik Priatini; I Nyoman Putu Budiartha; Johannes Ibrahim Kosasih; I Nyoman Alit Puspadma (Journal Equity of Law and Governance, 2024)
The problem that arises in this research is related to when Acquisition Duty of Right on Land and Building (BPHTB) payments occur and is related to the validity of the sale and purchase deed made by Lande Deed Officials (PPAT), which in this case is a problem, namely that there is a conflict of norms between Article 90 and Article 91 paragraph (1) of Regional Taxes and Regional Levies () Law. Based on these conditions, the legal issues raised are to examine and analyze (1) the philosophical basis of BPHTB in the process of buying and selling rights to land and/or buildings; (2) legal norms governing BPHTB payments in the process of buying and selling rights to land and/or buildings; and (3) reconstruction of BPHTB payment arrangements in the process of buying and selling rights to land and/or buildings legally. The research method used is the normative legal research method. The results of the research show that (1) The philosophical basis of BPHTB in the process of buying and selling rights to land and/or buildings is Pancasila and the 1945 Constitution of the Republic of Indonesia. The further philosophical basis is explicitly according to the General Explanation of the PDRD Law intended to encourage regional revenues and increase the effectiveness of BPHTB payments. Therefore, buyers of land rights are required to pay BPHTB first before a sale and purchase deed is drawn up by PPAT; (2) The legal norms governing BPHTB payments in the process of transferring rights to land and/or buildings through buying and selling are contained in Article 90 paragraph (1) letter a of the PDRD Law which conflicts with the norms of Article 91 paragraph (1) of the PDRD Law. The norm in Article 90 paragraph (1) letter a of the PDRD Law determines when the tax payable will be due to buyers of land rights. Meanwhile, Article 91 paragraph (1) of the PDRD Law requires buyers to pay BPHTB tax first before signing the sale and purchase deed before the PPAT. This is intended so that buyers comply with their obligations to pay BPHTB tax and to degrade the PPAT deed if it is signed before paying BPHTB tax, and (3) Reconstruction of BPHTB payment arrangements in the process of buying and selling rights to land and/or buildings legally can be carried out by amending the provisions of Article 91 paragraph (1) of the PDRD Law which allows buyers to have a sale and purchase deed made by PPAT, but PPAT is obliged to ensure that the buyer obediently pay BPHTB taxes. Novelty from the research is the reconstruction of Article 91 of the PDRD Law so that it is in accordance with Article 90 of the PDRD Law.